The Use of New Technologies in Speech Therapy Diagnosis and Therapy - a Research Report - Anna Michniuk; Maria Faściszewska (Edukacja Elementarna w Teorii i Praktyce)
The main aim of this paper is to present experiences and opinions of Polish speech therapists on the use of modern technology in speech therapy and diagnosis. A total of 105 participants (n=105) took part in the online survey conducted from March to October 2023. The study showed that Polish speech therapists, in the 6 months preceding the survey, had never used modern technology when diagnosing their patients (32.4% responses) or had done rarely (35.2% responses). The situation is different for speech therapy. 47.6% of the respondents answered that during the six months preceding the survey, they had often used modern technology when working with patients, 5.7% of the respondents indicated that they had always done so. 8.6% of respondents had never conducted speech therapy sessions using modern technology, and 29.5% answered that they had done so rarely. The results showed also that Polish speech therapists have divergent opinions on the use of ICT in their profession, some see it as an opportunity, while others see it technology overload.